2015
DOI: 10.1088/0026-1394/52/2/376
|View full text |Cite
|
Sign up to set email alerts
|

Planar electrical-substitution carbon nanotube cryogenic radiometer

Abstract: We have developed a fully-lithographic electrical-substitution planar bolometric-radiometer (PBR) that employs multiwall vertically-aligned carbon nanotubes (VACNT) as the absorber and thermistor, micro-machined Si as the weak thermal link and thin-film Mo as the electrical heater. The near-unity absorption of the VACNT over a broad wavelength range permits a planar geometry, compatible with lithographic fabrication. We present performance results on a PBR with an absorption of 0.999 35 at 1550 nm, a thermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The second type of device under development is a fully microfabricated carbon-nanotube PBR on a micromachined silicon substrate, with integrated thin film thermistor and heater. PBRs of this type have been well-described in a series of recent papers [14,18,19], and a general schematic is shown in figure 7. Time constants for devices of this type have been measured to be as small as 12 ms at 6 K, and could be significantly less in future planned designs.…”
Section: Detector Designsmentioning
confidence: 96%
See 1 more Smart Citation
“…The second type of device under development is a fully microfabricated carbon-nanotube PBR on a micromachined silicon substrate, with integrated thin film thermistor and heater. PBRs of this type have been well-described in a series of recent papers [14,18,19], and a general schematic is shown in figure 7. Time constants for devices of this type have been measured to be as small as 12 ms at 6 K, and could be significantly less in future planned designs.…”
Section: Detector Designsmentioning
confidence: 96%
“…The long time constants have been driven by the need to absorb nearly all the incident light, which is most readily accomplished by engineering the receiver as a light-trapping cavity with significant thermal inertia. A faster design, the electrically-substituted bolometer (ESB), however, has more recently exploited highly absorbing films such as gold-black [13] or vertically-aligned carbon nanotubes [14] to accomplish near-unity absorption over a broad spectral range using a thin film structure on a planar receiver. Time constants have already been reduced to about 10 ms, and further reductions are possible with further miniaturization and use of substrates made from membranes.…”
Section: Time Constants and Es Techniquesmentioning
confidence: 99%
“…Nearly one hundred years later, the electrical substitution radiometer demonstrated by Martin et al, of the National Physical Laboratory (NPL) in the United Kingdom became the definitive standard for absolute optical power measurements [3]. Tomlin et al, at the National Institute of Standards and Technology (NIST) more recently demonstrated that it is possible to achieve all of the essential elements of an absolute radiometer, consisting of a carbon nanotube absorber, thermistor, heater and weak thermal link; all on a microfabricated chip for optical fiber power measurements [4]. In the present work, we extend the work of Tomlin to freefield far infrared (FIR) or terahertz (THz) radiometry.…”
Section: A Brief History Of the Cryogenic Radiometermentioning
confidence: 99%
“…For example, 150 μW / k. G = at 52 kΩ. We estimate a time constant of approximately 30 ms based on the properties of a comparable heat capacity from Tomlin et al [4]. In the present scheme of electrical substitution, the temporal response is limited by the resistance bridge at 300 ms and 1 s sampling rate of the PI control.…”
Section: Vanta Thermistor Noise and The Radiometer's Thermal Conductancementioning
confidence: 99%
“…As an example, we have recently demonstrated an absolute cryogenic electrical substitution radiometer. 2 Its principle is based on direct comparison of optical power to its electrical equivalent. It consists of a black absorber connected to a heat reservoir with stable temperature through a weak thermal link.…”
Section: Introductionmentioning
confidence: 99%